Seed Characteristics and Nutritional Composition of Pine Nut from Five Populations of P. cembroides from the States of Hidalgo and Chihuahua, Mexico - Valero Galván, José (2019)
The aim of this study was to analyze the seed characteristics and nutritional composition of five pine nut P. cembroides samples from two Mexican states. Morphometry, proximal composition, phenolic compounds, and antioxidant capacity were determined. Samples differed in several morphometric trails, but important differences were documented between SMCH and JCZH samples from Hidalgo State. JCZH and FMH had the highest contents of water, lipids, protein, flavonoids, and antioxidant activity, while CMCC population from Chihuahua State had presented the highest content of ash and carbohydrates. Morphometry and chemical composition data were subjected to clustering analysis. This analysis showed that SMCH and LFCH from Hidalgo State were well separated from the JCZH and FMH populations from Hidalgo State, which showed a strong similarity between them, while the CMCC from Chihuahua State was the most distant population. Principal components analysis showed that the variables that strongly contributed to PC1 were the antioxidant activity determined by FRAP assay, flavonoids, and water content. These data have provided biochemical markers that could help to establish phylogenetic associations between populations, and also to reveal potentially account as an alternative source for dietary nutrition.